(untitled) (Actualizaciones en Sida e Infectología, 2021)
Antimicrobial resistance is a serious global health problem. It is even more critical in hospitals due to the emergence of multi-drug resistant Gram negative bacteria, associated with high mortality. The treatment options in these cases are scarce, generally high cost. The high density of antibiotic consumption and cross-transmission in this environment amplifies this problem. There is more evidence of the impact of Infection Control measures than of Antimicrobial Committee interventions to mitigate it. Furthermore, few countries have solid Infection Control programs to deal with this problem. This review proposes a series of 12 steps to adopt to mitigate the prevalence of antimicrobial resistance and reduce the incidence of carbapenemases in health institutions. These recommendations should be interpreted as a ¨Bundle¨ or package of measures, in which all are important. Those that involve the prevention of infections and / or colonizations and their dissemination are the ones with the greatest impact demonstrated so far. It is essential that antimicrobial use optimization programs have the empowerment of the leadership of the institutions where they are carried out, as well as that they are constituted by an efficient multidisciplinary team, solidly trained, with objective goals and metrics and periodic audits. It is also recommended that recommendations be included for treatments in patients in end-of-life care.